Over a million students use our free study notes to help them with their homework
Rewrite as y = 2 / (x^2 + 2). Swap all x and y symbols to create x = 2 / (y^2 + 2). Rearrange for y to reach y=g(x)=sqrt( (2-2x) / x ).
This is an example of differentiation. With differentiation the key rule that allows us to differentiate most algebraic functions is "times the coefficient by the power then decrease the power by one...
Firstly, ff(8) is the same as f(f(8)) so f(8) needs to be found first. Subbing in x=8 f(8)=22/3, so f(22/3) is required, Setting x=22/3 f(22/3)= 20/(22/3 - 5) = 60/7. so ff(8)=60/7.Next, as x tends to in...
Write sin3(x) as sin2x*sinx and differentiate using product rule, u=sin2x, vAnswered by Liam R. • Maths tutor2570 Views
a+3b = 15, a+11b=47 , use simultaneous equations to get 8b = 32 therefore b=4 and a=3.
←
439
440
441
442
443
→
Internet Safety
Payment Security
Cyber
Essentials